2005
DOI: 10.1038/nature03485
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the DNA damage checkpoint and genomic instability in human precancerous lesions

Abstract: DNA damage checkpoint genes, such as p53, are frequently mutated in human cancer, but the selective pressure for their inactivation remains elusive. We analysed a panel of human lung hyperplasias, all of which retained wild-type p53 genes and had no signs of gross chromosomal instability, and found signs of a DNA damage response, including histone H2AX and Chk2 phosphorylation, p53 accumulation, focal staining of p53 binding protein 1 (53BP1) and apoptosis. Progression to carcinoma was associated with p53 or 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

103
1,787
1
41

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,875 publications
(1,932 citation statements)
references
References 27 publications
103
1,787
1
41
Order By: Relevance
“…The possible existence of an ATM-dependent surveillance system for Bcl-2 in breast cancer development is consistent with recent findings showing that activation of ATM is an early event in lung and bladder cancer initiation, and that attenuation of ATM function promotes the cancer progression (Bartkova et al, 2005;Gorgoulis et al, 2005). The proposed mechanism for ATM activation in lung and bladder tumorigenesis is DNA replication stress imposed by abnormal cell cycle progression, which produces DNA damage and therefore activation of ATM.…”
Section: Bcl-2 Activates Atm In Mcf-7 Cellssupporting
confidence: 88%
See 1 more Smart Citation
“…The possible existence of an ATM-dependent surveillance system for Bcl-2 in breast cancer development is consistent with recent findings showing that activation of ATM is an early event in lung and bladder cancer initiation, and that attenuation of ATM function promotes the cancer progression (Bartkova et al, 2005;Gorgoulis et al, 2005). The proposed mechanism for ATM activation in lung and bladder tumorigenesis is DNA replication stress imposed by abnormal cell cycle progression, which produces DNA damage and therefore activation of ATM.…”
Section: Bcl-2 Activates Atm In Mcf-7 Cellssupporting
confidence: 88%
“…Ataxia telangiectasia mutated protein signaling contributes to oncogenemediated activation of p14 ARF -p53 (Li et al, 2004). Oncogene-driven abnormal cell-cycle progression was found to activate ATM in precancerous lesions of the lung and bladder and attenuation of this ATM surveillance system facilitates cancer development (Bartkova et al, 2005;Gorgoulis et al, 2005). In breast cancer, phosporylation of Chk2 at the ATM phosphorylation site, Thr68, was detected in the absence of irradiation (DiTullio et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…MECs within CERM D1À/À TEBs expressed markers of an activated DNA damage response The occurrence of a DNA damage response can be ascertained by immunohistochemical detection of wellcharacterized antibodies such as serine 139-phosphorylated histone H2AX (gH2AX), threonine 68-phosphorylated Chk2 (pT-Chk2) and serine 15-phosphorylated p53 (pS-p53) (Bartkova et al, 2005;Gorgoulis et al, 2005). The mean percentage of MECs within TEBs demonstrating nuclear-localized gH2AX was significantly higher in CERM D1À/À (8.3%±1.0) compared to CERM glands (0.97%±0.27) (P ÂŒ 0.001, MannWhitney test; Figures 5a-c).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that cyclin E overexpression causes DNA damage and checkpoint activation (Spruck et al, 1999;Ekholm-Reed et al, 2004;Bartkova et al, 2005;Minella et al, 2007). Aberrant stimulation of cell proliferation leads to DNA replication stress, doublestrand breaks, genomic instability, activation of DNA damage checkpoints and p53-dependent apoptosis or cell cycle arrest to ensure genomic integrity (Gorgoulis et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It is envisaged that centromeric regions intrinsically present replication barriers due to the condensed structure of heterochromatin, and unresolved replication barriers and/or asynchronous replication may result in DNA damage such as DNA double-strand breaks (Leach et al, 2000). Overstimulation of cell proliferation pathways has been shown to generate replication stress and DNA double-strand breaks at regions difficult to replicate, due to the conflict between unscheduled DNA synthesis and uncoordinated prereplicative complex assembly (Bartkova et al, 2005;Gorgoulis et al, 2005). Indeed, p16 INK4a deletion, which promotes cell proliferation, is detected in both of our telomerase-immortalized cell lines (Li et al, 2006;Cheung et al, 2010).…”
Section: Discussionmentioning
confidence: 99%